2021
DOI: 10.1002/mar.21522
|View full text |Cite
|
Sign up to set email alerts
|

Banks CSR‐fit, customers' quality of life, and cross‐buying: A joint moderation model

Abstract: The purpose of the current study is first to investigate attitudinal loyalty as a mediator of the relationship between corporate social responsibility (CSR)-fit and cross-buying, before examining the interaction of CSR-fit, CSR support, and quality of life in predicting cross-buying through attitudinal loyalty. In total, 821 bank customers provided data for this study by filling online and in-person surveys. The results from data analysis reveal that customers' perceived CSR-fit relationship with cross-buying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…An additional contribution of this study is that, while prior studies (see Zasuwa, 2017 for a review) employed firms' characteristics, and other CSR attributes such as consistency (Yoo & Lee, 2018) and support (Pérez & del Bosque, 2015) as potential moderators of the CSR perception‐customer outcome link, this study uniquely employs customers’ perception of QoL. In the same vein, QoL has mostly been considered as an outcome of CSR activities (Ogunmokun et al, 2021), this study contributes to the literature by investigating its role as an antecedent of customers’ response to CSR. Furthermore, this cross‐validation study demonstrated that the association between CSR‐fit and customer outcomes could be significantly different even for customers in different sectors within the same industry; further highlighting the complexity of the CSR‐fit concept.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional contribution of this study is that, while prior studies (see Zasuwa, 2017 for a review) employed firms' characteristics, and other CSR attributes such as consistency (Yoo & Lee, 2018) and support (Pérez & del Bosque, 2015) as potential moderators of the CSR perception‐customer outcome link, this study uniquely employs customers’ perception of QoL. In the same vein, QoL has mostly been considered as an outcome of CSR activities (Ogunmokun et al, 2021), this study contributes to the literature by investigating its role as an antecedent of customers’ response to CSR. Furthermore, this cross‐validation study demonstrated that the association between CSR‐fit and customer outcomes could be significantly different even for customers in different sectors within the same industry; further highlighting the complexity of the CSR‐fit concept.…”
Section: Discussionmentioning
confidence: 99%
“…As such, unlike MfB, CSR is included in C‐Banks’ strategies often as an addendum, and for its potential financial benefits (Illueca et al, 2009). Among the different forms of banks, the ones that contribute to the social economy such as MfBs represent a special case because of their twofold mission as a social organization and a business enterprise (Ademilua et al, 2020; Ogunmokun et al, 2021). For MfBs, CSR is no alien concept; it is the keystone of their culture, and it lies at the very heart of their core offerings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the study data were drawn from frontline employees working in Nigerian banks. As a result, the findings may not be generalizable to banking employees in other jurisdictions (Ogunmokun et al. , 2021).…”
Section: Discussionmentioning
confidence: 90%